2020
DOI: 10.18632/oncotarget.27494
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor CUX1 negatively regulates invasion in castrate resistant prostate cancer

Abstract: Metastatic prostate cancer is treated with androgen ablation therapy but progress to castrate resistant prostate cancer (CRPC). This study aimed to investigate the role of CUX1 in CRPC using clinical samples and in vitro models. CUX1 expression was increased in androgen-independent cells compared to androgen-sensitive cells. The multi-isoform nature of CUX1 makes it difficult to assay in tissue microarrays as there is no epitope able to distinguish the many isoforms for immunohistochemistry. Using surrogate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Knock-down of p200 in these cathepsin L-negative cells enhanced rather than suppressed invasiveness. This indicates that p110 promotes tumor progression, whereas p200, in the absence of cathepsin L, might exert tumor-suppressive actions [ 47 ]. It may be hypothesized that the delayed but also tumor-promoting phenotype seen in our p200 CUX1 mouse model is mediated by cathepsin L converting p200 into the active, tumor-promoting p110 variant.…”
Section: Discussionmentioning
confidence: 99%
“…Knock-down of p200 in these cathepsin L-negative cells enhanced rather than suppressed invasiveness. This indicates that p110 promotes tumor progression, whereas p200, in the absence of cathepsin L, might exert tumor-suppressive actions [ 47 ]. It may be hypothesized that the delayed but also tumor-promoting phenotype seen in our p200 CUX1 mouse model is mediated by cathepsin L converting p200 into the active, tumor-promoting p110 variant.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, a comprehensive study by interrogating total 7,651 genome sequences derived from 28 tumor types revealed nonsense and frameshift mutations in CUX1 in 1-5% of tumors and found that CUX1 deficiency can lead to activation of the pro-oncogenic PI3K-AKT signaling (93). In addition, CUX1 has been shown to negatively regulate invasion in castrate-resistant prostate cancer (94) and multidrug resistance in gastric cancer (95). It is worth mentioning that, although loss and/or inactivation of a CUX1 allele have been documented in many studies, there is so far no case of a tumor where both alleles have been lost or inactivated, suggesting the coexistence of an inactivated and an activated CUX1 alleles in tumor cells.…”
Section: Cux1 Acts As a Tumor Suppressormentioning
confidence: 99%
“…While p200 CUX1 protein increases after TGF-β treatment in normal lung fibroblasts, p75 does not 49 . Finally, in a study that reported that androgen-resistant prostate cancer cell lines upregulate p200, p75 was unchanged 50 . Collectively, these studies either fail to document an endogenous p75 protein, or uncouple the biology of p200 from p75.…”
Section: Discussionmentioning
confidence: 99%